Cu-doped polypyrrole hydrogel with tumor catalyst activity for NIR-II thermo-radiotherapy - Wang, Shile; Fei, Haotian; Ma, Yuhong; Zhu, Daoming; Zhang, Hongtao; Li, Xiang; Huang, Qinqin (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Radiotherapy (RT) is one of the key methods for treating breast cancer. However, the effect of single RT is often poor because of insufficient deposition of X-rays in tumor sites and radiation resistance induced by the abnormal tumor microenvironment (overexpression of glutathione (GSH)). The development of multifunctional RT sensitizers and synergetic therapeutic strategies is, therefore, a promising area for enhancing the anticancer effect of RT. Methods: In this study, a multifunctional nanozyme hydrogel based on Cu-doped polypyrrole (CuP) was designed to work concertedly with a second near-infrared thermal RT. The CuP-based hydrogel (CH) reached the tumor site when injected in-situ and achieved long-term storage. Results: Once stimulated with 1064-nm laser irradiation, the heated and softened hydrogel system released CuP nanozyme to provide photothermal therapy, thereby inhibiting the repair of DNA damage caused by RT. In addition, CuP with dual nanozyme activity depleted the intracellular GSH to reduce the antioxidant capacity of the tumor. Moreover, CuP converted H2O2 to produce ·OH to directly kill the tumor cells, thus enhancing the capability of low-dose RT to inhibit tumor growth. In vivo experiments showed that the CH system used in combination with a low-power 1064-nm laser and low-dose RT (4 Gy) exhibited good synergistic anticancer effects and biological safety. Discussion: As a new light-responsive hydrogel system, CH holds immense potential for radio-sensitization.